Relations Between Maternal Coping Socialization, Adolescents' Coping, and Symptoms of Anxiety and Depression. - Anderson, Allegra S.; Watson, Kelly H.; Reising, Michelle M.; Dunbar, Jennifer P.; Bettis, Alexandra H.; Gruhn, Meredith A.; Compas, Bruce E. (Journal of Child & Family Studies, 2021)
This study examined the associations among maternal socialization of coping, adolescents' coping, and adolescents' symptoms of anxiety and depression. A sample of 120 adolescents (45% female; M = 12.27; 66.7% White, 25% African American, 2.5% Asian American, 5.8% Latino or Hispanic American) and their mothers completed a series of questionnaires in a cross-sectional, multi-informant study. Findings indicate that maternal coping suggestions and adolescents' coping were both related to adolescents' anxiety/depression symptoms. Specifically, maternal socialization of secondary control coping messages was negatively correlated with adolescents' symptoms of depression and anxiety. Adolescents' use of secondary control coping emerged as the most robust correlate of symptoms, such that the use of secondary control coping was associated with fewer symptoms. The relationship between adolescents' coping strategies and their symptoms of anxiety/depression was associated with the extent to which mothers encouraged specific types of coping. Specifically, when mothers' socialization of secondary control coping was low, there was a negative association between adolescents' use of secondary control coping and symptoms. Furthermore, exploratory analyses suggest that specifically encouraging females to use secondary control coping strategies is adaptive, but how much daughters use secondary control coping has the strongest association with reduced internalizing symptoms. Collectively, the current findings indicate that there is an association between maternal coping suggestions and adolescents' symptoms of anxiety and depression, and there is a stronger association with adolescents' coping. Findings emphasize a need for researchers to further clarify the association of maternal coping suggestions with youth coping and adjustment as they navigate interpersonal stressors encountered during adolescence. Highlights: This study examined the relationship between parental socialization of coping, adolescents' coping, and internalizing symptoms using a multi-informant design. Results suggest that the interaction between maternal coping socialization and adolescent coping is associated with internalizing symptoms. Study results suggest that adolescents' use of adaptive coping strategies has the strongest association with their symptoms.